LED pumped Raman laser: Towards the design of an on-chip all-silicon laser. (March 2022) - Pradhan, Akash Kumar; Sen, Mrinal; Datta, Tanmoy
Highlights: A novel design of an LED pumped all-silicon Raman laser has been proposed. A self-consistent algorithm is presented for solving the coupled-mode equations. Transient, steady-state, and frequency domain responses of the laser are analyzed. Lasing threshold obtained is as small as 5 μw. Requirement of off-chip pump can be exterminated exploiting the electroluminescence. Abstract: Design of an on-chip silicon Raman laser is proposed based on a slotted photonic crystal nanocavity. The slot has been considered to be filled with the silicon nanocrystal material having ultra-high Raman gain coefficient, which has further been fortified by the tight spatio-temporal optical confinement inside the nanocavity. Consequently, the threshold power as required for the lasing is miniaturized substantially, and a light emitting diode (LED) suffices for optical pumping. The LED is amenable for integration on the same platform as of the silicon nanocrystal embedded slotted photonic crystal nanocavity exploiting the efficient electroluminescence of the silicon nanocrystal material. The coupled mode equations for stimulated Raman scattering interactions, which govern the evolution of the pump and the Stokes photons, have been solved using a novel self-consistent algorithm to analyze the characteristics of the proposed laser. A lasing threshold-power, as small as, 5 μW has been achieved. Moreover, small-signal frequency response of the proposed LED pumped laser has also been evaluated in steady-state condition, and a modulation bandwidth as high as ∼ 1.6 GHz has been demonstrated which is almost two orders of magnitude higher than that of the conventional Raman lasers.